Audubon field notes for winter 1964-1965 contributed by Frederick W. Kent - Kent, Frederick W. (Frederick Wallace), 1894-1984et al (1964)
Audubon field notes for Iowa City, Iowa area contributed by Frederick W. Kent. The winter population was at a minimum level and fewer birds were reported at bird feeders. Seven Saw-whet owls were sighted and a possible Glaucous Gull. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1965. Epson - sheet feed/flatbed